Cidadania cultural e políticas culturais no Brasil: uma análise da participação da Comissão Nacional dos Pontos de Cultura (CNPdC) de 2004 a 2014 - Silva, Bárbara Michelle Duarte Teixeira Lira da (2022)
The objective of this work is to analyse the project of cultural citizenship and participation in public cultural policy entitled “Culture Points” implemented by the Ministry of Culture (MinC) during the Workers Party (PT) government (2004-2014). Our focus is on the relationship between the National Commission of Culture Points and the Ministry of Culture (MinC) investigating the manner in which the project of “administrative co- participation” presupposed by MinC occurred in fact as well as the role of civil society representatives in the construction and the possible alteration of the state culture policy agenda. During the PT administration, there was an attempt to develop a public cultural policy in terms of “cultural citizenship” as a basic social right of the citizen in opposition to a neoliberal conception that treats culture as a commercial question determined by the laws of the market. We observe in Brazilian cultural policy a conflict between on the one hand a focus on cultural citizenship and the advance in the constitution of cultural rights and on the other state centralism and fragility of civil society; the result of an incomplete or precarious citizenship in other spheres. Thus, the study reveals the obstacles and challenges for a cultural policy directed towards cultural citizenship in the context of an incomplete or blocked citizenship.